The Effect of Tranquilizers on Morphological Parameters of Chicken Blood - Ibragimova Feruza Davletbaevna,; Abdurakhmonova Mokhichekhra, (American Journal of Biology and Natural Sciences, 2025)
This study investigates the effects of the anti-stress drugs nozepam, enrofloxacin, and aliceryl on the morphological parameters of chicken blood. The objective was to evaluate changes in key hematological indicators under the influence of these preparations. Experimental groups of chickens were administered the respective drugs according to established veterinary dosage protocols, and blood samples were collected for laboratory analysis. Hematological parameters, including erythrocyte and leukocyte counts, hemoglobin concentration, and other morphological indices, were measured using standard diagnostic methods. The results demonstrated that the application of the tested drugs influenced blood morphology to varying degrees, indicating physiological responses associated with stress modulation and metabolic adaptation. The findings suggest that these preparations may affect hematological stability and should be used with consideration of their systemic impact. The study contributes to understanding the hematological effects of anti-stress pharmacological agents in poultry production.